Developing Self-Assessment with Mobile Learning-Based to Improve Learning Achievement of Indonesian Madrasah Competency Assessment at Madrasah Ibtidaiyah - Dian Eka Aprilia Fitria Ningrum; Nur Hidayah Hanifah; Like Raskova Octaberlina; Silvia Ellyana (UIN Siber Syekh Nurjati Cirebon, 2025)
AbstractThe Minimum Competition Assessment (AKM) is a replacement for the existence of the National Examination. AKM is designed to achieve student learning outcomes through cognition, especially related to literacy and numeracy. However, there is still a problem that students experience difficulties in doing AKM or AKMI (Indonesian Madrasah Competency Assessment) questions at school. Therefore, this research provides a solution by developing learning media in the form of a mobile learning-based application using the ADDIE method. The subjects in this study are grade IV students of Madrasah Ibtidaiyah Nurul Jadid Blitar, East java, Indonesia. According to the study's findings, learning experts' validation results are 93%, media experts' validation results are 96%, and material experts' validation results are 98%. According to student learning outcomes, the SIASAT application can improve student learning outcomes; the average pretest score in the control class is 56, and the posttest average score is 79.2. Meanwhile, in the experimental class, the average pretest score was 56, and the posttest average score was 87.8. Meanwhile, based on the calculation of the T-test, a significant value of 0.042 > 0.05 was obtained. This indicates that students can enhance their learning outcomes by using mobile learning-based self-assessment media to deal with AKMI.Keywords: AKMI, madrasah ibtidaiyah students, mobile learning, self-assessment. AbstrakAsesmen Kompetensi Minimal (AKM) merupakan pengganti keberadaan Ujian Nasional. AKM dirancang untuk mencapai capaian pembelajaran siswa melalui kognisi, terutama terkait literasi dan numerasi. Namun, masih terdapat permasalahan yaitu siswa mengalami kesulitan dalam mengerjakan soal-soal AKM atau AKMI (Asesmen Kompetensi Madrasah Indonesia) di sekolah. Oleh karena itu, penelitian ini memberikan solusi dengan mengembangkan media pembelajaran berupa aplikasi berbasis mobile learning dengan metode ADDIE. Subjek dalam penelitian ini adalah siswa kelas IV Madrasah Ibtidaiyah Nurul Jadid Blitar, Jawa Timur, Indonesia. Berdasarkan hasil penelitian, hasil validasi ahli pembelajaran sebesar 93%, hasil validasi ahli media sebesar 96%, dan hasil validasi ahli materi sebesar 98%. Berdasarkan capaian pembelajaran siswa, aplikasi SIASAT dapat meningkatkan capaian pembelajaran siswa; rata-rata skor pretes pada kelas kontrol sebesar 56, dan rata-rata skor postes sebesar 79,2. Sementara itu, pada kelas eksperimen, rata-rata skor pretes adalah 56, dan rata-rata skor postes adalah 87,8. Berdasarkan perhitungan uji-T, diperoleh nilai signifikansi 0,042 > 0,05. Hal ini menunjukkan bahwa mahasiswa dapat meningkatkan hasil belajarnya dengan menggunakan media asesmen mandiri berbasis pembelajaran seluler untuk menghadapi AKMI.Kata kunci: AKMI, siswa madrasah ibtidaiyah, pembelajaran mobile, penilaian mandiri.